The Role of CXCR3 and Its Chemokine Ligands in Skin Disease and Cancer - Kuo, Paula T.; Zeng, Zhen; Salim, Nazhifah; Mattarollo, Stephen; Wells, James W.; Leggatt, Graham R. (Frontiers in Medicine, 2018)
Chemokines and their receptors play an important role in the recruitment, activation and differentiation of immune cells. The chemokine receptor, CXCR3, and its ligands, CXCL9, CXCL10, and CXCL11 are key immune chemoattractants during interferon-induced inflammatory responses. Inflammation of the skin resulting from infections or autoimmune disease drives expression of CXCL9/10/11 and the subsequent recruitment of effector, CXCR3+ T cells from the circulation. The relative contributions of the different CXCR3 chemokines and the three variant isoforms of CXCR3 (CXCR3A, CXCR3B, CXCR3alt) to the inflammatory process in human skin requires further investigation. In skin cancers, the CXCR3 receptor can play a dual role whereby expression on tumour cells can lead to cancer metastasis to systemic sites while receptor expression on immune cells can frequently promote anti-tumour immune responses. This review will discuss the biology of CXCR3 and its associated ligands with particular emphasis on the skin during inflammation and carcinogenesis.